1978
DOI: 10.1111/j.1471-4159.1978.tb10448.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Vanillylmandelic Acid and 3‐methoxy‐4‐hydroxy‐phenylglycol in the Rat Brain

Abstract: Abstract— The effects of electrothermic destruction and electrical stimulation of the locus coeruleus on the brain levels of vanillylmandelic acid (VMA), 3‐methoxy‐4‐hydroxyphenylglycol (MOPEG) and noradrenaline (NA) were studied in the rat. Fourteen days after destruction of the locus coeruleus, the content of NA in the hippocampus and that of MOPEG in the rest of the brain were decreased by more than 70% and 50% respectively. Stimulation of the locus coeruleus induced a decrease in hippocampal levels of NA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In a number of biochemical studies in the rat using lesion techniques both ipsi-and contralateral effects have been reported (Ad~r, Muskiet, Jeuring, and Korf, 1978;Arbuthnot% Christie, Crow, Eccleston, and Walter, 1973;Buda, Roussel, Renaud, and Pujol, 1975;Kobayashi, Palkovits, Kopin, and Jacobowitz, 1974;Korf, Roth, and Aghajanian, 1973;Korf, Aghajanian, and Rot~a, 1973;Walter and Eccleston, 1973;Worth, Collins, Kett, and Austin, 1976). Fourteen days after unilateral destruction of the rat LC we (Ad~r, Postema, and Korf, 1979) observed higher cortical and hippocampal levels of NE in the intact side, when compared to control values of sham-operated animals.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a number of biochemical studies in the rat using lesion techniques both ipsi-and contralateral effects have been reported (Ad~r, Muskiet, Jeuring, and Korf, 1978;Arbuthnot% Christie, Crow, Eccleston, and Walter, 1973;Buda, Roussel, Renaud, and Pujol, 1975;Kobayashi, Palkovits, Kopin, and Jacobowitz, 1974;Korf, Roth, and Aghajanian, 1973;Korf, Aghajanian, and Rot~a, 1973;Walter and Eccleston, 1973;Worth, Collins, Kett, and Austin, 1976). Fourteen days after unilateral destruction of the rat LC we (Ad~r, Postema, and Korf, 1979) observed higher cortical and hippocampal levels of NE in the intact side, when compared to control values of sham-operated animals.…”
Section: Introductionmentioning
confidence: 93%
“…(2) To obtain biochemical evidence for such projections by a correlation analysis of ipsi-and contralateral alterations of hippocampal and cortical NE and of forebrain 3-methoxy-4-hydroxyphenylglycol (MHPG), a major metabolite of NE, induced by unilateral electrical stimulation of the LC, as these levels are sensitive indices of release of NE (Korf, Roth, and Agha)anian, 1973;Ad~r, Muskiet, Jeuring, and Korf, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Although electrical stimulation is also known to increase the synthesis of NA (Roth et al, 1974), this elevated amine synthesis is probably not sufficient to replenish the functional pool. Indeed, previous experiments have revealed that electrical stimulation of the locus ceruleus causes a depletion of cortical and hippocampal endogenous tissue levels of about 30% (Korf et al, 1973;Ader et al, 1978). An alternative explanation may be that at high frequencies of stimulation the large amounts of NA released into the synaptic cleft stimulate presynaptic inhibitory or,-autoreceptors leading to a feedback inhibition and thus to a limitation of the amine release.…”
Section: Amentioning
confidence: 99%
“…Norepinephrine (NE) is metabolized by monoamine oxidase (EC 1.4.3.4) to aldehyde intermediates which, in mammalian brain, are preferentially reduced rather than oxidized (Karoum et al, 1976;Ader et al, 1978). The product formed is 3,4-dihydroxyphenylglycol (DHPG) and, if 0-methylated in addition, 3-methoxy-4-hydroxyphenylglycol (MHPG) (Rutledge and Jonason, 1967;Braestrup et al, 1974).…”
mentioning
confidence: 99%